PTH-033 FCSEMS for liver transplant biliary strictures are associated with a high risk of post-ERCP pancreatitis. Issue 2 (June 2019) - Johnston, Chris; Church, Nicholas; Bow, Samantha; Wigmore, Stephen
Abstract : Introduction: Benign biliary strictures are a common complication of liver transplantation, mainly as a result of constriction at the site of biliary anastomosis or ischaemic cholangiopathy. Placement of fully covered self-expanding metal stents (FCSEMS) by ERCP has been shown to be an effective treatment for benign and malignant biliary strictures and offers advantages over plastic stents of greater patency rates and the potential for stricture remodeling. The aim of this study was to assess the incidence of post-ERCP pancreatitis following placement of FCSEMS for benign biliary strictures after liver transplantation in a high-volume centre. Methods: Retrospective analysis of prospectively maintained local databases was performed. Endoscopy reports were reviewed for every ERCP (any indication) performed for liver transplant recipients between 1stJanuary 2014 and 1st January 2018. Patient outcomes were gathered from electronic patient records. Severity of pancreatitis was graded according to the Revised Atlanta Classification. Statistical comparison of two groups was performed with Fisher's exact test. Results: Over a four-year period, 36 out of 393 consecutive liver transplant recipients underwent ERCP for treatment of benign biliary strictures. A total of 97 ERCPs were performed for this patient group (mean 2.7 per patient, range 1–13). Placement of temporary fully covered self-expanding metal stents successfully achieved long-term stricture resolution in 92% of patients (22/24). However, ERCP involving placement of a first FCSEMS was associated with a considerably higher rate of post-ERCP pancreatitis than any other ERCP performed in this study population (34.5% vs 2.8%, P<0.0001); 89% (8/9) of episodes of pancreatitis were classified as mild, 11% (1/9) as severe. Conclusions: In the experience of a single high-volume centre, placement of FCSEMS by ERCP is an effective treatment for the management of benign biliary strictures, but one that is associated with a particularly high risk of pancreatitis. Patients should give informed consent accordingly. Further research into the mechanisms behind this effect (e.g. sudden occlusion of a normal pancreatic duct) and the effectiveness of additional specific prophylactic measures is underway.